Comparison of conventional and organic paddy cropping systems in South Sulawesi, Indonesia - Nurliani Nurliani; Ida Rosada; Sitti Rahbiah; Sitti Nurani Sirajuddin; Abdel Razzaq M. Al-Tawaha; Abdel Rahman Mohammad Said Al-Tawaha (SAINS TANAH - Journal of Soil Science and Agroclimatology, 2025)
Rice is the food source for the community, including in the South Sulawesi area. Consequently, proper management is needed to support optimal production results. Several farmers are currently starting to develop organic farming systems due to the shortcomings of the conventional farming system such as the use of chemical inputs, land degradation, and decreased production. This study aims to compare the organic farming developed by farmers with conventional farming systems in terms of land ownership, input, soil quality, and productivity. This research used a simple random sampling method to collect land and production data from 130 farmers (90 conventional, 40 organic).In general, in South Sulawesi, the organic farming system is better than conventional farming systems. The inputs in the conventional are certified seeds, chemical fertilizers, and pesticides, which will affect costs and have an effect in the long term. Meanwhile, in an organic farming system, seed needs are met independently by farmers, using organic materials (manure, compost, bokashi) and biopesticides. Productivity also shows that the organic farming system increases production than conventional farming. In the future, farmers can start to develop an organic farming system by adding various organic ingredients to support their field performance.